Depressive Symptoms Associated With Musculoskeletal Pain in Inactive Adults During COVID-19 Quarantine - Christofaro, Diego G.D. [UNESP]; Tebar, William R. [UNESP]; da Silva, Gabriela C.R. [UNESP]; Oliveira, Max Duarte; Cucato, Gabriel G.; Botero, João Paulo; Correia, Marilia A.; Ritti-Dias, Raphael M.; Lofrano-Prado, Mara C.; Prado, Wagner L. (My University, 2022)
Background: Depression has been associated with episodes of musculoskeletal pain. However, it is not clear whether such relationships could be mitigated according to the physical activity level. Aim: To describe, during the COVID-19 pandemic, the relationship between depression and musculoskeletal pain according to the physical activity levels. Design: Cross-sectional study. Methods: This research was conducted in Brazil between May 5 and March 17, 2020. Participants (N = 1872; 58% women) were invited through social media to answer a structured online questionnaire. Depressive symptoms were assessed through self-report of perception of depression during quarantine. Musculoskeletal pain was assessed based on the Nordic questionnaire identifying nine possible pain points in the body. Physical activity was assessed based on the weekly frequency, intensity, and duration of each session of physical activity the participants engaged in during COVID-19. The logistic binary regression analyzed the associations between depressive symptoms and musculoskeletal pain according to the participants’ level of physical activity. Results: Depressive symptoms were associated with pain in six different regions of the body in physically inactive participants. In physically inactive participants, those with depressive symptoms 1.51 (95% CI = 1.04-2.19) and 2.78 (95% CI = 1.81-4.26) times more likely to have pain in one or two and ≥three regions body regions, respectively. In active participants, depressive symptoms were not associated with pain. Conclusion: During the COVID-19 pandemic, depression was associated with musculoskeletal pain in physically inactive participants.